1998
DOI: 10.1056/nejm199809103391102
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Appetite-Suppressant Drugs and the Risk of Cardiac-Valve Regurgitation

Abstract: The use of fenfluramine or dexfenfluramine, particularly for four months or longer, is associated with an increased risk of newly diagnosed cardiac-valve disorders, particularly aortic regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(114 citation statements)
references
References 11 publications
2
108
0
4
Order By: Relevance
“…Of note, cardiac valve dysfunction associated with fenfluramine and dexfenfluramine therapy was clearly evident among patients treated for 6 months (2). More recent studies confirm the development of valvular heart disease in patients treated with fenfluramine for as little as 4 months and also suggest a higher prevalence in patients treated for longer periods (3). In the present study, selecting for only patients treated with sibutramine for 2 180 days did not suggest any increase in the incidence of valvular heart disease, suggesting that duration of therapy was not a significant limitation.…”
Section: Study Limitationssupporting
confidence: 74%
“…Of note, cardiac valve dysfunction associated with fenfluramine and dexfenfluramine therapy was clearly evident among patients treated for 6 months (2). More recent studies confirm the development of valvular heart disease in patients treated with fenfluramine for as little as 4 months and also suggest a higher prevalence in patients treated for longer periods (3). In the present study, selecting for only patients treated with sibutramine for 2 180 days did not suggest any increase in the incidence of valvular heart disease, suggesting that duration of therapy was not a significant limitation.…”
Section: Study Limitationssupporting
confidence: 74%
“…The longterm safety of antiobesity medications is also a concern given previous evidence linking fenfluramine and dexfenfluramine to valvular heart disease and pulmonary hypertension, and recent concerns regarding sibutramine and increased cardiovascular risk. [24][25][26][27][28] Given the rising prevalence of obesity and the potential for more widespread use of antiobesity drugs, we sought to review the available evidence regarding the long-term efficacy and safety of such agents.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive use of fluoxetine for long-term treatment of depression, there have been no reports of cardiac valve lesions similar to those seen with fenfluramine and dexfenfluramine. 4,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Rothman et al 51 suggested that serotonergic drugs that bind to 5-HT (2B) receptors were associated with cardiac valve lesions. Fenfluramine and dexfenfluramine were among those that bound to 5-HT (2B) receptors, but fluoxetine did not.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Weight losses at 1 year were approximately 15-17% of initial body weight with phen-fen [3][4][5][6][7][8][9] compared to losses of 6-10% of initial body weight with single-drug treatment using fenfluramine. [10][11][12][13][14][15][16][17][18][19] When fenfluramine and dexfenfluramine were removed from the market in September 1997 because of concerns about cardiac valve lesions, 4,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] some physicians turned to combinations of phentermine and other serotonin-active drugs such as fluoxetine and sertraline in an attempt to reproduce the phen-fen effect. However, there are very few studies published on the efficacy of these combinations for obesity, and none have compared results with phen-fen.…”
Section: Introductionmentioning
confidence: 99%